Strength evaluation of the Prussian vaults made from brick aggregate concrete - Vladimir Bespalov; Romuald Orlovich; Rafal Nowak; Nikolai Vatin (Инженерно-строительный журнал, 2018)
The behavior of Prussian vaults of brick aggregate concrete differs both from the behavior of brick vaults and classical flat slabs. Such vaults are particularly susceptible to physical damage and deterioration. To determine the real bearing capacity of the vaults, the authors not only performed the insitu determination on several sections with deflection control, but also numerical simulations of the multispan system of Prussian vaults in the program complex Abaqus. Moreover, experimental comparisons between damaged and not damaged vaults were also performed in the historical building of the New Holland complex. Obtained results show that, the vaults adjacent to the loaded one exhibit opposite behavior and significant damages caused by the loaded one, both of which are useful outcomes for evaluation of this vaulting type.